Pengaruh Sales promotion dan Interaksi Parasosial terhadap Keputusan Pembelian: Studi Kasus Pengguna TikTok Shop di Kota Bandung - Dinda Aulia Azzahra; Angga Nadiyanto Prastian (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The rapid expansion of live commerce has transformed TikTok Shop into a platform where promotional strategies and host–consumer interactions play an increasingly important role in shaping purchasing behavior. This study investigates the influence of sales promotion and parasocial interaction on the purchase decisions of TikTok Shop users in Bandung, Indonesia. A quantitative research design was employed using survey data collected from 100 respondents who had previously purchased products through TikTok Shop. The data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption tests. The findings reveal that both sales promotion and parasocial interaction exert a positive and statistically significant influence on purchase decisions. Sales promotion demonstrated a significant partial effect (t = 4.244, p < 0.001), while parasocial interaction also showed a significant positive effect (t = 3.630, p < .001). Simultaneously, the two variables significantly explained variations in purchase decisions (F = 25.785, p < 0.001). These findings indicate that consumers are more likely to complete purchases when attractive promotional incentives are accompanied by meaningful interactions with live-streaming hosts. The study highlights the importance of integrating promotional programs with interactive communication strategies to enhance consumer conversion within social commerce platforms.